(untitled) (Quinto Sol, 2022)
This article analyses two constitutional reforms in the province of Buenos Aires, those of 1989-1990 and the one approved in 1994, in a general sense, in the light of the institutional changes they proposed in relation to previous experiences and the political-social challenges of the present and, in a specific sense, with regard to the debates and issues concerning the status of the Church and the Catholic religion. The text addresses three dimensions for each reform: a contextual one, which recovers the constitutional texts in relation to the process of democratization initiated in 1983 without losing sight of the national reformist horizon; another that looks at the way in which the provincial reforms incorporate transformations driven by the economic, social and political changes since the institutional recovery; and one concerned with the construction of secularism, which will consider the presence and importance of the principles defended by the Church in the constitutional debates.